Knowledge, Barriers, and Motivation Related to Breast and Cervical Cancer Screening Among Women in Bojonegoro, East Java: A Qualitative Study - Afriza Umami; Sudalhar Sudalhar; Tegar Wahyu Yudha Pratama; Istiqlal Fitri; Andan Firmansyah (Journal of Health Promotion and Behavior, 2020)
Background: Breast and cervical cancer remain a major cause of morbidity and mortality for women in Indonesia. Although this cancer can be detected early, women are still less active in self-detecting breast and cervical cancer, so both cancers are found at an advanced stage. This study aimed to explore how women's knowledge, barriers, and motivations are related to early detection of breast and cervical cancer.Subjects and Method: This was a qualitative study, with focus group discussions (FGDs) and interviews with key informants. Discussions and interviews were conducted in the community within Ledok Kulon village, Bojonegoro Regency, East Java, Indonesia. Participants: FGD participants involved 20 women, 10 women underwent FDG about cervical cancer and 10 other women conducted FGD about breast cancer. Three key informants interviewed with health worker and administrator that allow triangulation of responses thereby increasing the validity of the findings. Participants were aged 20 to ≥60 years, with no history of symptoms or previous diagnosis of breast or cervical cancer. The women were interviewed in October-November 2019. The transcribed data were analyzed using content analysis.Results: Participants' knowledge about understanding, risk factors, signs and symptoms of breast and cervical cancer was still lacking. Participants attributed the cause of cervical cancer to the vaginal wound resulting in cervical cancer and signs of symptoms such as heartburn. Whereas for breast cancer participants were not know the signs and symptoms, they only said there was a lump in the breast. Barriers to screening were ashamed to be examined by health workers, afraid of testing procedures, feeling healthy and there were no signs of cancer. Screening motivation were experiencing signs and symptoms of cancer, family history of the disease and awareness of the disease/screening service.Conclusion: The study participants' knowledge of breast and cervical cancer was still lacking. To improve breast and cervical cancer screening, efforts must focus on reducing identified barriers and increasing motivation.Keywords: knowledge, barriers, motivation, breast and cervical cancer screeningCorrespondence: Afriza Umami. Diploma III of Medical Records, School of Health Sciences Muhammadiyah Bojonegoro, Jl. A.Yani No.14, Bojonegoro, Indonesia. Email: afrizaumami20@gmail.com. Mobile: +6282254348041.Journal of Health Promotion and Behavior (2020), 5(1): 1-10 https://doi.org/10.26911/thejhpb.2020.05.01.01